2015
DOI: 10.1515/intox-2015-0014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of the aqueous stem bark extract of Bridelia ferruginea (Euphorbiaceae) in rodents

Abstract: Bridelia ferruginea is a woody shrub that grows in the Savannah or rain forests of Africa and has traditionally been used to treat diabetes, arthritis and boils. Despite all these uses, extensive toxicological evaluation has not been carried out. The aim of the present investigation was to evaluate the sub-chronic toxicological effects of the stem bark aqueous extract of Bridelia ferruginea in rats. The lethal dose (LD50) was determined using probit analysis and graded doses of the extract (250–4000 mg/kg) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
6
14
3
Order By: Relevance
“…The various hematologic parameters accustomed assess the toxic potential of plant extract in men and animals [34].…”
Section: Discussionmentioning
confidence: 99%
“…The various hematologic parameters accustomed assess the toxic potential of plant extract in men and animals [34].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, B. ferruginea and M. inermis have often been used to treat diabetes, malaria, dysentery and in animals, trypanosomiasis, diarrhoea, helminthosis [18][19][20][21][22]. Moreover, previous work has shown that both plants are not toxic [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The weights of liver and kidney in all groups under observation slightly increases i.e (treated with ciprofloxacin and ethanol extract) when compared to the control(un-infected/untreated) except for the infected/treated where the weight was significantly reduced. [19] reported that since this is a non-significant increase in organ weights, by extrapolation and implication, the results may be an indication of the low toxicity and relative safety of the extract.Also, the increment in the relative weight of the kidney and liver reported in this study might be due to high presence of cardiac glycoside in the extract of B. ferruginea. Hence, this study agreed that its use should be controlled.…”
Section: Discussionmentioning
confidence: 86%
“…[26] stated granulocytes regulate the proliferation, differentiation and maturation of committed stem cells responsible for the production of WBC. Therefore, the decrease observed may imply that the ethanol stem bark extract of Bridelia ferruginea can cause immune suppression and also an impairment in the ability of the ethanol extract to stimulate the production of WBC s according to [19]. However, the significant increase (P< 0.05) in the group infected/un-treated with S. typhi was due to the fact that the rats were able to produced WBC which are capable of generating antibiotics in the process of phagocytosis and have high degree of resistance to diseases [23].…”
Section: Discussionmentioning
confidence: 99%